2008
DOI: 10.1371/journal.pone.0003556
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Hate

Abstract: In this work, we address an important but unexplored topic, namely the neural correlates of hate. In a block-design fMRI study, we scanned 17 normal human subjects while they viewed the face of a person they hated and also faces of acquaintances for whom they had neutral feelings. A hate score was obtained for the object of hate for each subject and this was used as a covariate in a between-subject random effects analysis. Viewing a hated face resulted in increased activity in the medial frontal gyrus, right p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 28 publications
(33 reference statements)
3
84
0
7
Order By: Relevance
“…Given previous studies of the cognitive functional role of the putamen, the activity in this area is significantly associated with intuitive social decision making and behavioral processes [38,39]. In addition, a previous study suggested that the putamen is associated with automatic emotional responses and processes, in particular, negative emotions, such as hate and disgust [49]. Thus, Korean participants apparently utilized socio-moral intuitive processes more strongly, and they more relied on an emotional intuitive circuit, which is associated with hate and disgust emotions when they were solving complicated and emotionally negative moral dilemmas, as suggested by the increased activity in the putamen.…”
Section: Discussionmentioning
confidence: 92%
“…Given previous studies of the cognitive functional role of the putamen, the activity in this area is significantly associated with intuitive social decision making and behavioral processes [38,39]. In addition, a previous study suggested that the putamen is associated with automatic emotional responses and processes, in particular, negative emotions, such as hate and disgust [49]. Thus, Korean participants apparently utilized socio-moral intuitive processes more strongly, and they more relied on an emotional intuitive circuit, which is associated with hate and disgust emotions when they were solving complicated and emotionally negative moral dilemmas, as suggested by the increased activity in the putamen.…”
Section: Discussionmentioning
confidence: 92%
“…As mentioned above, putamen is one of the areas of the brain which appears repeatedly in emotion-related experiments (Maddock 1999). Furthermore, this basal ganglion has been described as part of the hate circuit (Zeki and Romaya 2008), and it contributes to the pattern of activation that arises when studying the neural correlates of romantic love (Bartels and Zeki 2000).…”
Section: Synesthesia and Emotionmentioning
confidence: 98%
“…Moreover, a recent functional experiment about developmental grapheme-color synesthesia has shown unusual bilateral thalamic activation (Specht and Laeng 2011). Interestingly, recent evidence suggests that the thalamus and the basal ganglia may play a role in emotion (Carretie et al 2009;Lane et al 1997;Zeki and Romaya 2008). Therefore, the anatomy of subcortical structures is relevant to wholly understand the emotional component of synesthesia.…”
Section: Subcortical Contributions To Developmental Synesthesiamentioning
confidence: 99%
“…The role of putamen here resonates with the results of Alluri et al (2012), who found a preferential involvement of this basal ganglia structure in processing timbral ''brightness.'' It is suggestive to note that putamen has been implicated in aversive auditory reactions (Zald & Pardo, 2002) as well as strongly negative social-cognitive responses (Zeki & Romaya, 2008).…”
Section: Resultsmentioning
confidence: 98%